Implementasi Peraturan Talak dan Rujuk di Indonesia: Perspektif Surah Al-Baqarah Ayat 228, 229 dan 230 - Hariyadi, Riski (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research discusses the implementation of divorce and reconciliation regulations in Indonesia in the perspective of surah Al-Baqarah verses 228, 229 and 230. This research aims to find out specifically how the implementation of divorce and reconciliation regulations in Indonesia according to several commentators regarding surah Al-Baqarah verses 228, 229, and 230. The method used in this research is data collection method through library research. Data is collected by gathering information from various literature sources, including books, documentary materials, magazines, journals, and newspapers. From this research it can be concluded that the Marriage Law (UUP) and the Compilation of Islamic Law (KHI) regulate the procedures and conditions for rujuk in divorce. KHI pays attention to formal aspects such as the 'iddah period, reasons for rujuk, and women's rights, with in-depth interpretations from scholars such as Ath-Thabari, Ibn Kathir, and Al-Misbah. Divorce in Islam is regulated by both the KHI and the UUP, focusing on variations of divorce, such as talak raj'i and talak bain shughra. Al-Baqarah verse 229 provides a maximum limit on the granting of divorce, linking it to the 'iddah period, and affirming women's rights in the divorce process. Article 120 KHI addresses the serious consequences of divorce ba'in kubra (three-time divorce) which cannot be annulled outright. Although there is an opportunity to reunite after divorce ba'in kubra, the process involves marriage to a third party and divorce after passing the 'iddah period.